The Family Experiences in Caring for People with Mental Disorders - Putri, Dewi Kurnia (Journal of health research and technology, 2023)
Family has an important role as the main care provider for people with mental disorders. This study was to explore more deeply about the experience of families in caring for people with severe mental disorders. This research was qualitative research with a phenomenology method. The participants of this study were 3 people with more than 5 years of care for patients. Sampling technique using accidental sampling. The data collection method used in-depth interviews with Colaizzi data analysis techniques. The results obtained 6 themes. First, there was a family response in caring for ODGJ. Second there were changes in family activities. Third, problems experienced by families while caring for ODGJ consist of barriers to families experiencing mental disorders and barriers to seeking treatment from health services. Fourth, how to solved the problems experienced. The fifth theme is family expectations in caring for ODGJ. The last theme was treatment of ODGJ by the family consisting of differences in treatment of ODGJ and reasons for choosing treatment for ODGJ. This research can be used as a basic data for researchers to conduct further research to identify psychological problems experienced by families in caring for ODGJ